2018
DOI: 10.1038/s41375-018-0132-y
|View full text |Cite
|
Sign up to set email alerts
|

Serial minimal residual disease (MRD) monitoring during first-line FCR treatment for CLL may direct individualized therapeutic strategies

Abstract: Achieving undetectable MRD (U-MRD) status after chemoimmunotherapy predicts longer progression-free and overall survival. The predictive factors and timing of relapse in patients with U-MRD and value of interim MRD analysis are ill-defined. This was a prospective study of 289 patients with CLL treated first-line with FCR. MRD analysis was performed after course 3 (C3) and at end-of-therapy (EOT) in bone marrow using 4-color flow cytometry (sensitivity 10−4). Eighteen percent of patients had U-MRD after C3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…In addition, Thompson et al recently reported that undetectable MRD after course 3 of FCR predicted a greater likelihood of undetectable MRD at the end of therapy. 24…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Thompson et al recently reported that undetectable MRD after course 3 of FCR predicted a greater likelihood of undetectable MRD at the end of therapy. 24…”
Section: Discussionmentioning
confidence: 99%
“…All of these methods can provide information on MRD, which can help guide risk-adapted management and predict progression-free survival (PFS) and overall survival (OS) in patients. Accordingly, MRD is now routinely incorporated into clinical algorithms for several malignant hematologic diseases including MM [11], acute myeloid leukemia (AML) [12,13,14], ALL [15], and CLL [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the survival benefit associated with MRD-negative status regardless of the treatment used to attain it [8,18]. Most data were derived from studies of chemoimmunotherapy, including several large phase 3 randomized studies (CLL8, CLL10, CLL11) [8,16,[19][20][21], as well as smaller studies in both first-line and the relapsed settings [22,23]. Since the initiation of the GIBB trial, the use of ibrutinib has emerged as a preferred first-line treatment in older CLL patients.…”
Section: Discussionmentioning
confidence: 99%